Legionary Legates in Britain (with Some Remarks on the Division of the Province): The Cursus Honorum of Senators at the Turn of the Third Century AD in the Light of Modern Research - Okoń, Danuta (Polskie Towarzystwo Filologiczne, 2022)
At the turn of the 3rd century AD, there were three legions in Britain, commanded by senators. Their service in this position lasted for 2–3 years. Ten senators of the Severan period whose cursus featured the command of a legion in Britain have been identified. Five of them were homines novi, while five belonged to gentes senatoriae. They originated from Italy, Africa and the East (there were no representatives from the West). There is no clear single model for the career of a legionary legate in Britain, but we can say that it was an important function in the cursus honorum, giving people who held it good prospects for promotions (9 out of the 10 legates later became consuls). There were two provinces of Britain under the Severans: inferior (praetorian) with Legio VI victrix and superior (consular) with Legio II Augusta and XX Valeria victrix; the legate of Britannia inferior was not the legate of Legio VI victrix at the same time.